Early intervention and identification strategies for young people at risk of developing mental health issues: working in partnership with schools in Birmingham, UK. Issue 6 (21st August 2015) - Palmer, Colin J.; Connor, Charlotte; Newton, Benjamin John; Patterson, Paul; Birchwood, Max
Abstract: Aim: This study explores the mental health needs of teachers and how these might impact on their capacity to provide early identification and intervention strategies to support their student's emotional well‐being. Method: The present study surveyed a sample of UK teachers ( N  = 320) to explore the impact of work‐related stress on their mental health and their ability to provide early intervention support for their students. Results: Our survey showed high levels of work‐related stress due to time pressures and excessive workloads; many teachers failed to seek help for their stress often due to stigmatic attitudes and fear of negative response by senior management. Such factors led some to withdraw from taking on extra responsibilities with regard to student support and to consider leaving the teaching profession altogether. Coping mechanisms included the use of alcohol and tobacco, with only a small minority receiving access to psychological therapies. Conclusion: High levels of work‐related stress in teachers can have serious consequences for their mental health and impede their ability to provide effective early intervention support for their student's emotional well‐being. Improvements in mental health training for teachers and greater assistance for their own mental health needs are necessary.